Peningkatan Kemampuan Bercerita Menggunakan Media Gambar Pada Anak Usia 5-6 Tahun - Dianita, Shofitri Christina; Sari, Ayu Titis Rukmana; Lestariningrum, Anik (Universitas Nusantara PGRI Kediri, 2023)
Language has a very important contribution in the life of every individual. In almost every activity in an individual's life, it cannot be separated from aspects of language and speaking, including children with language disclosure through speaking, children can express their thoughts, feelings and expressions. The purpose of this study is to improve children's storytelling skills using picture media. This study used the classroom action research (CAR) method which consisted of four steps including: planning, implementing, observing, and reflecting. The data analysis used is a qualitative descriptive analysis technique. The success criterion in this study was increasing children's storytelling ability at the age of 5-6 years with an average mastery score of 75%. Based on the results of the action it can be concluded that children aged 5-6 years have experienced an increase in complete achievement. This is evidenced by the changes that occurred from the first cycle of 31.5%, the second cycle of 52.6% and the last cycle III reached 78.9% which indicates that the child's storytelling ability has increased from not appearing at first to appearing. This shows that picture media can improve children's storytelling skills.